Is closed thoracic drainage tube necessary for minimally invasive thoracoscopic-esophagectomy? - Cai, Lei; Li, Yan; Wang, Wen-Bin; Guo, Man; Lian, Xiao; Xiao, Shu-Ao; Xu, Guang-Hui; Yang, Xue-Wen; Sun, Li; Zhang, Hong-Wei (Journal of Thoracic Disease; Vol 10, No 3 (March 31, 2018): Journal of Thoracic Disease, 2018)
Background: Closed thoracic drainage tube (CTDT) is a conventional treatment after esophagectomy, even after minimally invasive esophagectomy. Here, we report a single-center, retrospective study to explore the safety and necessity of CTDT after thoracoscopic-esophagectomy. Methods: From October 2015 and August 2016, 50 patients were enrolled and underwent thoracoscopicesophagectomy in semi-prone position by same surgical team. Perioperative demographic and surgical parameters, and patients’ satisfaction with or without CTDT after thoracoscopic-esophagectomy were collected and analyzed. Results: All eligible patients (18 patients without CTDT and 32 patients with CTDT) were successfully underwent thoracoscopic procedures without conversion to open approach or major intraoperative complications and perioperative death. The two groups, with similar demographic parameters, had no statistically difference in thoracic operation time, blood loss, ICU stay, postoperative mobilization and oral feeding, and hospital stay. Also, the incidence of postoperative complications was similar with or without CTDT after esophagectomy. But, no-CTDT group had better post-operative satisfaction, including less pain scale scoring and better Norton scoring. Conclusions: This study demonstrated that the treatment of no-CTDT after the minimally invasive thoracoscopic-esophagectomy is safe and feasible, might reduce the work intensity of medical stuff and lead to a better patients’ experience.